Photocatalytic generation of gas phase reactive oxygen species from adsorbed water: Remote action and electrochemical detection. Issue 2 (April 2021) - Sun, Xinwei; Xu, Kaiqi; Chatzitakis, Athanasios; Norby, Truls
Abstract: The improvement of indoor environments is of great importance as it can significantly improve human health, comfort and productivity. Herein, different forms of TiO2 nanorods were used as the photocatalyst for generation of reactive oxygen species (ROS) in a gas phase photoreactor under controlled humidity. Several parameters were investigated by monitoring the remote decolourisation of Methylene Blue (MB) embedded in a Nafion film. A decolourisation of 26% under 80% relative humidity was observed when the MB film was 0.5 cm away from the photocatalyst. The length and ratio of light/dark intervals have major impacts on the efficiency of the gas phase photocatalytic process, which we link to the amount of water adsorbed on the photocatalyst, as the source for hydroxyl radicals. Furthermore, the photocatalytic production of ROS was quantified through a polyaniline electrochemical sensor and a rate of 1 · 10 12 of ROS molecules s −1 was estimated. This study contributes to the efficacy of the gas phase photocatalytic method in air decontamination, for the development of efficient air cleaning devices. Graphical Abstract: ga1 Highlights: Gas phase photocatalytic generation of reactive oxygen species by adsorbed water layers. Remote decolourisation of a solid methylene blue film in varying relative humidity. The role of adsorbed water as reactant for generation of ROS is discussed. Photogeneration of ROS is estimated in-situ by an electrochemical polyaniline sensor.